The Interrelation Between Responsible Research and Innovation Dimensions and Macro Indicators - Bagočiūnė, Laura; Novelskaitė, Aurelija (Vilnius University Proceedings, 2023)
Responsible Research and Innovation (RRI) concept has become an important topic in the academic community and in policy circles (van de Poel et al., 2017) and encompasses six main policy agendas (or dimensions): ethics; gender equality; governance; open access; public engagement; science education (RRI Tools, 2023). RRI concept, including gender (equality) as one of the dimensions, still lacks empirical explorations-based understanding. This paper aims to explore the peculiarities of interrelations between gender (equality) as one dimension of the Responsible Research and Innovation and societal progression in gender equality and innovativeness on macro level. Starting with generating original data-base of [n – 214] indicators quantitative secondary data analysis of descriptive characteristics of the selected variables and (Spearman) correlation (RS) analysis between the variables was accomplished. Descriptive and correlation analysis of interrelations between women’s involvement in four R&I (i.e. Business, Higher education, Governmental and Private Non-profit) sectors and Gender Equality Index and Global Innovation Index in 2013–2020 shows rather small changes of the indicators and fragmental interrelations between them during the period.